Nitric Oxide-releasing Sulindac is a Novel Skin Cancer Chemopreventive Agent for UVB-induced Photocarcinogenesis - Chaudhary, Sandeep C. (2012)
Nitric oxide (NO)-releasing non-steroidal anti-inflammatory drugs (NO-NSAIDs) which have been synthesized to reduce gastro-intestinal and cardiovascular toxicities of NSAIDs, possess anti-proliferative, pro-apoptotic and anti-cancer activities. Here, we show that NO-sulindac inhibited UVB-induced skin tumorigenesis in SKH-1 hairless mice. Topical application of NO-sulindac reduced tumor incidence, number (p<0.05) and volume (p<0.005) as compared to UVB (alone)-irradiated vehicle-treated mice. An increase in TUNEL-positive cells in skin lesions was accompanied by the enhanced Bax:Bcl-2 ratio. The expression of pro-apoptotic Bax was increased whereas anti-apoptotic Bcl-2 reduced. However, proliferation was identified as the major target of NO-sulindac in this study. A reduced expression of PCNA and cyclin D1 associated with the dampening of cell cycle progression was observed. The mechanism of this inhibition was related to the reduction in UVB-induced Notch signaling pathway. UVB-induced inflammatory responses were diminished by NO-sulindac as observed by a remarkable reduction in the levels of phosphorylated MAP Kinases Erk1/2, p38 and JNK1/2. In this regard, NO-sulindac also inhibited NFκB by enhancing IκBα as evidenced by the reduced expression of iNOS and COX-2, the direct NFκB transcription target proteins. NO-sulindac significantly diminished the progression of benign lesions to invasive carcinomas by suppressing the tumor aggressiveness and retarding epithelial-mesenchymal transition. A marked decrease in the expression of mesenchymal markers such as Fibronectin, N-cadherin, SNAI, Slug and Twist and an increase in epithelial cell polarity marker E-cadherin were noted in NO-sulindac-treated tumors. Our data suggest that NO-sulindac is a potent inhibitor of UVB-induced skin carcinogenesis and acts by targeting proliferation-regulatory pathways.